Signal Transduction Mechanisms for Glucagon-Induced Somatolactin Secretion and Gene Expression in Nile Tilapia (Oreochromis niloticus) Pituitary Cells - Zhang, Chaoyi; Lian, Anji; Xu, Yue; Jiang, Quan (Frontiers in Endocrinology, 2021)
Glucagon (GCG) plays a stimulatory role in pituitary hormone regulation, although previous studies have not defined the molecular mechanism whereby GCG affects pituitary hormone secretion. To this end, we identified two distinct proglucagons, Gcga and Gcgb, as well as GCG receptors, Gcgra and Gcgrb, in Nile tilapia (Oreochromis niloticus). Using the cAMP response element (CRE)-luciferase reporter system, tilapia GCGa and GCGb could reciprocally activate the two GCG receptors expressed in human embryonic kidney 293 (HEK293) cells. Quantitative real-time PCR analysis revealed that differential expression of the Gcga and Gcgb and their cognate receptors Gcgra and Gcgrb was found in the various tissues of tilapia. In particular, the Gcgrb is abundantly expressed in the neurointermediate lobe (NIL) of the pituitary gland. In primary cultures of tilapia NIL cells, GCGb effectively stimulated SL release, with parallel rises in the mRNA levels, and co-incubation with the GCG antagonist prevented GCGb-stimulated SL release. In parallel experiments, GCGb treatment dose-dependently enhanced intracellular cyclic adenosine monophosphate (cAMP) accumulation with increasing inositol 1,4,5-trisphosphate (IP3) concentration and the resulting in transient increases of Ca2+ signals in the primary NIL cell culture. Using selective pharmacological approaches, the adenylyl cyclase (AC)/cAMP/protein kinase A (PKA) and phospholipase C (PLC)/IP3/Ca2+/calmodulin (CaM)/CaMK-II pathways were shown to be involved in GCGb-induced SL release and mRNA expression. Together, these results provide evidence for the first time that GCGb can act at the pituitary level to stimulate SL release and gene expression via GCGRb through the activation of the AC/cAMP/PKA and PLC/IP3/Ca2+/CaM/CaMK-II cascades.